China's SMEs Developed Characteristics and Countermeasures in the Post-epidemic Era - Su, Wunhong; Guo, Xiaohan; Ling, Yunxia; Fan, Yi-Hao (Frontiers in Psychology, 2022)
Due to the COVID-19 outbreak, a series of chain reactions, like international trade breakdown, stock market collapse, and crude oil’s collapse, have adversely affected the global economy, particularly small and medium-sized enterprises (SMEs). As a result, the Chinese government issued many fiscal and financial policies to support SMEs. This paper analyzes SMEs' coping methods and conceptual changes affected by the epidemic and distinguishes "victims" and "beneficiaries." Subsequently, based on extensive international experience and local government experience, it provides effective suggestions for the Chinese government to deal with the post-epidemic era's economic changes, policy suggestions, and coping strategies for SMEs' short-term and long-term sustainable development.